Characterization of some Winery by-Products Used in Animal Feeds - Raluca Paula Turcu; Margareta Olteanu; Mariana Ropota; Monica Mitoi; Dumitru Drăgotoiu (Scientific Papers Animal Science and Biotechnologies, 2023)
Secondary products from winemaking are considered to be a rich source of bioactive compounds, mainly phenolic compounds, which can offer numerous opportunities to improve feed quality. This paper aims to characterize three winery by-products (grape marc, grape seed meal and grape seed oil) with regard to: the primary chemical composition; polyphenol content; antioxidant capacity; fatty acid profile and amino acid profile. Grape marc had 10.43% crude protein, significantly lower (P<0.05) compared to grape seed meal (12.70%). The polyphenols content was significantly different (P<0.05) between the tested raw materials, the highest concentration being found in the grape seed meal (28.05 mg EAG/g) and the smallest in the grape seed oil (0.28 mg EAG/g). Consequently, the antioxidant capacity significantly differentiated (P<0.05) among all raw materials, the highest value of 145.83 mM Trolox / g being recorded at grape seed meal, followed by 9.44 mM Trolox / g in grape marc and 0.70 Mm Trolox / g to grape seed oil. The highest lysine content (0.58 g/100 g SU) was recorded in the marc, while the cystine (0.24 g/100 g SU) was recorded in grape seed grains. The obtained results show that these winery by-products can be used as natural antioxidants in animal feed.